Impact of carbon revenue on EU gross domestic product - Zukauskiene, Joana; Snieska, Vytautas (Transformations In Business & Economics, 2026)
Carbon taxes motivate consumers to choose carbon-neutral or green options, such as energy-efficient technologies or renewable energy sources, which are considered environmentally safer compared to carbon-intensive alternatives. Carbon taxes encourage manufacturers to invest in cleaner production methods and technologies and to innovate. Today, more than 70 carbon dioxide pricing schemes are in place worldwide, but their contribution to emissions reduction remains a subject of intense debate in politics and science. Carbon dioxide pricing reduces greenhouse gas emissions, but its effectiveness depends on the context of implementation and policy. Not all schemes are equally efficient. The purpose of the study is to investigate the relation of carbon tax revenue and gross domestic product. The research problem and the gap in the literature arise because existing scientific work typically examines carbon dioxide pricing only as a means of reducing emissions or analyses the use of revenues for social or environmental programmes, but does not examine its influence on GDP, investment, or economic growth. Research objective: to investigate the impact of carbon taxation revenue on gross domestic product based on the consequences of carbon taxation analysis.